Quantitative Structure–Retention Relationships for Polycyclic Aromatic Hydrocarbons and their Oligoalkynyl‐Substituted Derivatives. Issue 4 (13th July 2017) - Rouillé, Gaël; Jäger, Cornelia; Huisken, Friedrich; Henning, Thomas; Czerwonka, Regina; Theumer, Gabriele; Börger, Carsten; Bauer, Ingmar; Knölker, Hans‐Joachim
Abstract: Reversed‐phase high‐performance liquid chromatography (RP‐HPLC) has been carried out for a series of unsubstituted polycyclic aromatic hydrocarbons (PAHs) and the corresponding ethynyl, 1, 3‐butadiynyl, and 1, 3, 5‐hexatriynyl derivatives. Theoretical values of the isotropic polarizability and several polarity descriptors have been computed for each compound by using semiempirical models and density functional theory (DFT), with the aim of evaluating linear functions as quantitative structure–retention relationships (QSRRs). The polarity has been described by using either the permanent electric dipole moment, the subpolarity, or a topological electronic index. Three types of partial atomic charges have been used to calculate the subpolarity and a topological index. The choice of the theoretical model, of the polarity descriptor, and of the partial atomic charges is discussed and the resulting QSRRs are compared. Calculating the retention times from the polarizability and the topological electronic index (AM1, PM3, or DFT‐B3LYP/6–31+G(d, p)) gives the best agreement with the experimental values. Abstract : Retention times of PAHs : The polarizability and the polarity of polycyclic aromatic hydrocarbons (PAHs) and their oligoalkynyl‐substituted derivatives are computed to provide quantitative structure–retention relationships (QSRRs) from reversed‐phase (RP)‐HPLC measurements. The best QSRRs are based on a linear correlation of the retention time t R with the isotropic polarizability α and the polarity T E, which can be calculated either by using DFT or the semiempirical models AM1 and PM3.